SOCIO-ECONOMIC DIMENSION OF FISH FARMING IN ASSAM - Sathiadhas, R.; Goswami, U. C.; Goswami, Mukunda; Ojha, S. N. (Journal of Indian Fisheries Association, 2015)
Information on socio-economic framework of the fishfarmercommunity forms a benchmark for policy formulation to develop thiseconomically backward sector. Very few studies have been conducted on thesocio-economic aspect of fish farming. Two districts of Assam, Darrang andNagaon, were selected for this study where 120 respondents from each districtwere selected randomly. The characteristics representing the personnel andsocio-economic attributes of the fishfarmers are presented in this paper. Thesocio-economic status of fish farmers has to be improved by bringing themodern concepts of fish farming to the doorstep of farmers.Keywords: Socio-economics, fish culture